The potential for multi-disciplinary primary health care services to take action on the social determinants of health: actions and constraints - Baum, Frances E; Legge, David G; Freeman, Toby; Lawless, Angela; Labonté, Ronald; Jolley, Gwyneth M (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background The Commission on the Social Determinants of Health and the World Health Organization have called for action to address the social determinants of health. This paper considers the extent to which primary health care services in Australia are able to respond to this call. We report on interview data from an empirical study of primary health care centres in Adelaide and Alice Springs, Australia. Methods Sixty-eight interviews were held with staff and managers at six case study primary health care services, regional health executives, and departmental funders to explore how their work responded to the social determinants of health and the dilemmas in doing so. The six case study sites included an Aboriginal Community Controlled Organisation, a sexual health non-government organisation, and four services funded and managed by the South Australian government. Results While respondents varied in the extent to which they exhibited an understanding of social determinants most were reflexive about the constraints on their ability to take action. Services’ responses to social determinants included delivering services in a way that takes account of the limitations individuals face from their life circumstances, and physical spaces in the primary health care services being designed to do more than simply deliver services to individuals. The services also undertake advocacy for policies that create healthier communities but note barriers to them doing this work. Our findings suggest that primary health care workers are required to transverse “dilemmatic space” in their work. Conclusions The absence of systematic supportive policy, frameworks and structure means that it is hard for PHC services to act on the Commission on the Social Determinants of Health’s recommendations. Our study does, however, provide evidence of the potential for PHC services to be more responsive to social determinants given more support and by building alliances with communities and social movements. Further research on the value of community control of PHC services and the types of policy, resource and managerial environments that support action on social determinants is warranted by this study’s findings.